From tailwinds to headwinds: Emerging and developing economies in the twenty-first century - Mirco Balatti Mozzanica; M. Ayhan Kose; Kate McKinnon; Edoardo Palombo; Naotaka Sugawara; Guillermo Verduzco-Bustos; Dana Vorisek (Koç University-TÜSIAD Economic Research Forum (ERF), 2025)
The first quarter of the twenty-first century has been transformative for emerging market and developing economies (EMDEs). These economies now account for about 45 percent of global GDP, up from about 25 percent in 2000, a trend driven by robust collective growth in the three largest EMDEs - China, India, and Brazil (the EM3). Collectively, EMDEs have contributed about 60 percent of annual global growth since 2000, on average, double the share during the 1990s. Their ascendance was powered by swift global trade and financial integration, especially during the first decade of the century. Interdependence among these economies has also increased markedly. Today, nearly half of goods exports from EMDEs go to other EMDEs, compared to one-quarter in 2000. As cross-border linkages have strengthened, business cycles among EMDEs and between EMDEs and advanced economies have become more synchronized, and a distinct EMDE business cycle has emerged. Cross-border business cycle spillovers from the EM3 to other EMDEs are sizable, at about half of the magnitude of spillovers from the largest advanced economies (the United States, the euro area, and Japan). Yet EMDEs confront a host of headwinds at the turn of the second quarter of the century. Progress implementing structural reforms in many of these economies has stalled. Globally, protectionist measures and geopolitical fragmentation have risen sharply. High debt burdens, demographic shifts, and the rising costs of climate change weigh on economic prospects. A successful policy approach to accelerate growth and development should focus on boosting investment and productivity, navigating a difficult external environment, and enhancing macroeconomic stability.
Keywords: E32; E60; F02; F44; O11; 330; Economic growth; business cycle synchronization; spillovers of business cycles; emerging markets; developing economies; global integration; macroeconomic policies; All these keywords